A Proposed Scale for Assessing the Investment Risk - Mourhij, Mounzer (جامعة العربي بن مهيدي أم البواقي - مخبر المالية، المحاسبة، الجباية والتأمين, 2023)
في إطار علاقة المبادلة بين العائد والمخاطرة وحاجة متخذي قرارات الاستثمار إلى قياس المخاطر باستخدام مقاييس متنوعة، فقد وجد الباحث ثمة نقاط ضعف في استخدام بعض المقاييس التقليدية وعدم موضوعيتها في قياس المخاطر الحقيقية، مما دفعه إلى اقتراح مقياس جديد لتقييم المخاطر وقياسها. وقد قام الباحث بتوصيف المقياس المقترح وتوضيح آلية عمله وتجربته من خلال عشر حالات افتراضية، وقد أظهرت نتائج تجريب المقياس وجود اختلافات كبيرة بين المقياس المقترح والمقاييس التقليدية المقارنة مثل الانحراف المعياري ومعامل الاختلاف، والتي أظهرت أن المقياس المقترح كان أكثر موضوعية في تقييم المخاطر وقياسها وإظهار المفهوم الحقيقي للمخاطر. In the context of of trade-off between return and risk, the investment decision makers need to measure risks using various measures, the researcher found weaknesses in using some traditional measures and their lack of objectivity in measuring real risks, which prompted him to propose a new scale for assessing and measuring risks. The researcher described the proposed scale, explained its mechanism of action, and experimented it through ten virtual cases. The results of testing the scale showed that there were significant differences between the proposed scale and the traditional comparative measures such as the standard deviation and the coefficient of variance, which showed that the proposed scale was more objective in assessing and measuring risks and demonstrating the real concept of risk. The researcher also tested the ability of the scales to distinguish between the studied cases and assess the degree of risk for each of them using the relative interquartile deviation, where the proposed scale outperformed the other measures, as the value of the relative interquartile deviation of the proposed scale was %118.31, while it was %3.13 for the standard deviation and %3.22 for the coefficient of variation.
Keywords: إدارة المخاطر -- مخاطر الاستثمار -- المؤسسات المالية